Pengaruh Pemberian Aromaterapi Ginger Oil (Zingiber officinale) Terhadap Emesis Gravidarum Pada Ibu Hamil Trimester I Di Klinik Makmur Jaya Tahun 2019 - Carolin, Bunga Tiara (Jurnal Kesehatan Qamarul Huda, 2019)
In the first trimester, it is likely that women will experience nausea with or without vomiting. This symptom starts around the sixth week of pregnancy and usually drops dramatically at the end of the first trimester, one way to deal with nausea in pregnant women is by giving ginger oil which contains essential oils that have a refreshing effect, blocking vomiting reflexes, blood circulation and make the nerves work properly.This study aimed to determine the effect of using ginger oil on emesis gravidarum among first trimester pregnant women in the Makmur Jaya Clinic in 2019.This quasi-experimental study used the design of the One Group Pretest-Posttest Design. The sample in this study were 30 first trimester pregnant women who experienced nausea. The sampling technique used was total sampling. The research instrument was a PUQE score to assess the degree of nausea and vomiting among pregnant women. Data were analyzed using descriptive statistics, namely paired t-test. The results showed that there were a significant difference in the degree of nausea of ??pregnant women before and after intervention in the experimental group (p <0.05). the Conclusions showed Ginger oil can reduce the degree of nausea among pregnant women. This program can be applied in midwifery practice, especially for pregnant women in the first trimester with complaints of nausea and as a references for future research.